HUBUNGAN IMUNISASI, ASI EKSKLUSIF, DAN PERAN KADER DENGAN TUMBUH KEMBANG BALITA DI PUSKESMAS JEULINGKE TAHUN 2021 - Masthura, Syarifah; Iskandar, Iskandar; Safwan, Laila (Jurnal Ilmiah Keperawatan, 2022)
Reports from the Jeulingke Health Center show that mothers do not know the benefits of immunization for babies to prevent babies from infectious diseases, mothers avoid transmission of covid 19 by not going to posyandu, mothers do not know how to increase breast milk when having babies so that babies do not get exclusive breastfeeding for 6 months. As for the lack of health promotion on immunization and exclusive breastfeeding by village cadres, this has an impact on the growth and development of toddlers such as malnutrition and stunting. The purpose of the study was to determine the relationship between immunization, exclusive breastfeeding, and the role of cadres with the growth and development of toddlers at the Jeulingke Health Center, Banda Aceh City in 2021. The research design was descriptive correlational with a sample of 93 respondents using proportional sampling. This research was conducted from May to June 2021. The results showed that there was a relationship between immunization (P = 0.000), exclusive breastfeeding (P = 0.000), and the role of cadres (P = 0.009) with the growth and development of toddlers. toddlers at the Jeulingke Health Center in Banda Aceh City. 2021. It is recommended for the puskesmas to hold counseling at the posyandu to mothers about the importance of immunization for toddlers and the importance of breastfeeding for child growth and development, while the puskesmas involves the role of cadres in providing such couunseling